2014
DOI: 10.1017/s0029665114001591
|View full text |Cite
|
Sign up to set email alerts
|

Optimal vitamin D levels in Crohn's disease: a review

Abstract: Vitamin D deficiency is common among patients with Crohn's disease. Serum 25-hydroxyvitamin D (25(OH)D) is the best measure of an individual's vitamin D status and current cut-off ranges for sufficiency are debatable. Several factors contribute to vitamin D deficiency in Crohn's disease. These include inadequate exposure to sunlight, inadequate dietary intake, impaired conversion of vitamin D to its active metabolite, increased catabolism, increased excretion and genetic variants in vitamin D hydroxylation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 138 publications
(177 reference statements)
4
20
0
6
Order By: Relevance
“…Multivariable analysis revealed a significant association between elevated MUST score and a lower 25-hydroxy vitamin D level (p=0.032). The relationship between IBD and vitamin D has recently become a controversial topic of intense research, summarized well in several recent reviews [23][24][25][26]. In general, epidemiologic studies have demonstrated a high prevalence of vitamin D deficiency/insufficiency among patients with IBD (regardless threshold level used) and conversely, a higher vitamin D level is associated with a lower risk of CD [22].…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable analysis revealed a significant association between elevated MUST score and a lower 25-hydroxy vitamin D level (p=0.032). The relationship between IBD and vitamin D has recently become a controversial topic of intense research, summarized well in several recent reviews [23][24][25][26]. In general, epidemiologic studies have demonstrated a high prevalence of vitamin D deficiency/insufficiency among patients with IBD (regardless threshold level used) and conversely, a higher vitamin D level is associated with a lower risk of CD [22].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple observational studies have established that vitamin D exerts a protective effect in the colon through its active metabolite 1,25D [4245]. Vitamin D deficiency is associated with increased hospitalization and surgery in IBD patients [46]. Vitamin D supplementation prevents relapse via an effect on intestinal permeability and improves muscle strength, fatigue, and quality of life in patients with Crohn’s disease [46].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency is associated with increased hospitalization and surgery in IBD patients [46]. Vitamin D supplementation prevents relapse via an effect on intestinal permeability and improves muscle strength, fatigue, and quality of life in patients with Crohn’s disease [46]. A correlation exists between serum levels of 25D as a result of nutritional intake and/or exposure to sunlight and incidence of CRC, and higher plasma vitamin D levels are correlated with a reduced risk of CRC [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…In bestimmten Situationen, beispielsweise bei Adipositas, bei Einnahme von Antikonvulsiva oder unter Glukokortikoidtherapie, kann diese Dosis verdoppelt oder sogar verdreifacht werden. Gerade unter einer Glukokortikoidtherapie kann der Vitamin-D-Spiegel sinken, sodass er entweder kontrolliert werden sollte oder täglich 1000 IE 25-OH-Vitamin D supplementiert werden sollten [726,727]. [728].…”
Section: Therapie Des Vitamin-d-mangelsunclassified